Pemanfaatan Ekstrak Ubi Jalar Ungu dan Ekstrak Kulit Melinjo sebagai Pewarna Alami pada Sediaan Lip Cream - Astuty, Meilinda Windy; Purnama, Uwan; Pauzi, Dini Eka; Saumi, Rizkina Salsabila; Zulkifli, Anggraeni Putri Rahayu; Permana, Cinta Aurellia; Hanifah, Nurul; Kania, Risti; Maharani, Elisa Intan; Destiani, Syilda (Pakis Journal Institute, 2025)
Lip cream is a type of lip makeup that has a liquid texture but tends to be thick or creamy. For this reason, lip cream is often referred to as liquid lipstick. The community service event held on January 30, 2025, at SMA Negeri 4 Cimahi involved 32 students and aimed to provide insights into the utilization of natural resources in the production of lip cream. The activity began with an opening and introduction, followed by a presentation on the use of purple sweet potato (Ipomoea batatas L) and melinjo fruit skin (Gnetum gnemon, L) as active ingredients in the lip cream formulation. Lip cream, which has the ability to keep lips moisturized longer than solid products, is expected to meet good cosmetic standards, namely not causing irritation and providing an even color. The students learned about the anthocyanin content in purple sweet potatoes, which serves as a natural dye, as well as the antimicrobial compounds in melinjo skin that function as preservatives. The resulting lip cream formulation shows a balance between active ingredients and additives, along with organoleptic test results that indicate the desired characteristics. This activity not only provided new knowledge to the students about the utilization of natural ingredients but also fostered their awareness of the importance of safety and quality in the cosmetic products they use. Through a question-and-answer session and the distribution of the